3, 5, 4′-Tri-O-acetylresveratrol Attenuates Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome via MAPK/SIRT1 Pathway. (16th November 2015) - Ma, Lijie; Zhao, Yilin; Wang, Ruixuan; Chen, Tingting; Li, Wangping; Nan, Yandong; Liu, Xueying; Jin, Faguang
Abstract : The aim of the present research was to investigate the protecting effects of 3, 5, 4′-tri-O-acetylresveratrol (AC-Rsv) on LPS-induced acute respiratory distress syndrome (ARDS). Lung injuries have been evaluated by histological examination, wet-to-dry weight ratios, and cell count and protein content in bronchoalveolar lavage fluid. Inflammation was assessed by MPO activities and cytokine secretion in lungs and cells. The results showed that AC-Rsv significantly reduced the mortality of mice stimulated with LPS. Pretreatment of AC-Rsv attenuated LPS-induced histological changes, alleviated pulmonary edema, reduced blood vascular leakage, and inhibited the MPO activities in lungs. What was more, AC-Rsv and Rsv treatment reduced the secretion of TNF- α, IL-6, and IL-1 β in lungs and NR8383 cells, respectively. Further exploration revealed that AC-Rsv and Rsv treatment relieved LPS-induced inhibition on SIRT1 expression and restrained the activation effects of LPS on MAPKs and NF- κ B activation both in vitro and in vivo. More importantly, in vivo results have also demonstrated that the protecting effects of Rsv on LPS-induced inflammation would be neutralized when SIRT1 was in-hibited by EX527. Taken together, these results indicated that AC-Rsv protected lung tissue against LPS-induced ARDS by attenuating inflammation via p38 MAPK/SIRT1 pathway.